Genetic and Phenotypic Variation Studies Among Half-sib Progenies of Eucalyptus tereticornis - Thakur, Ajay; Sidhu, Dalbara Singh (Indian Forester, 2010)
Being suitable species for timber production, genetic improvement programme of Eucalyptus tereticornis was started in Punjab Agricultural University, Ludhiana by selecting superior phenotypes and raising their progeny trial. In this study, phenotypic and genetic variation of 18 months old half-sib progenies of 17 selected plus trees were assessed for the height (m) and collar diameter (cm). The maximum mean height and mean collar diameter were 2.50 m and 2.20 cm respectively in family no 16. The individual tree heritability for height and collar diameter was estimated 0.30 and 0.24 respectively, while the family heritability was 0.65 for height and 0.60 for collar diameter. The phenotypic and genetic (additive) variance among the families for the height was 0.38 and 0.11 respectively, while it was 0.64 and 0.15 for collar diameter. The phenotypic coefficient of variability was 29.10 % for height and 46.75 % for collar diameter while the genetic (additive) coefficient of variability was 15.86 % and 22.72 % for height and collar diameter respectively. The estimated genetic gain was 0.49 m and 0.50 cm for height and collar diameter respectively.